Postoperative nursing management of a patient with perianal necrotizing fasciitis and multiple complications (1例肛周坏死性筋膜炎合并多种并发症患者的术后护理体会) - XU Yunxia (许云霞); LI Yudong (李宇栋); PEI Xiaolu (裴晓璐); FAN Yanan (范亚楠); WANG Shuo (王烁) (中西医结合护理)
This paper summarized the postoperative nursing management of a patient with perianal necrotizing fasciitis and multiple complications. The patient was received Traditional Chinese Medicine debridement, Chinese herbal medicine fumigation and washing, auricular point pressing therapy and comprehensive nursing interventions on gout-related symptoms, anaphylactoid purpura, pain, dietary, emotion and health education. The nursing interventions based on integration of Traditional Chinese and western medicine were effective to improve the postoperative rehabilitation of the patient. (本文总结1例肛周坏死性筋膜炎(PNF)合并多种并发症患者的术后护理经验, 包括中医化腐清创治疗、中药局部熏洗、耳穴压丸、痛风护理、过敏性紫癜的护理、疼痛护理、饮食护理、情志护理以及健康宣教等, 通过开展中西医结合多元化的护理措施, 促进患者早日康复。)